Aircraft design a conceptual approach - Raymer, Daniel P. 1954- (AIAA education series, 2018)
"Aircraft Design: A Conceptual Approach, Sixth Edition by AIAA Fellow Dr. Daniel P. Raymer provides updates to what has become a standard textbook and reference throughout the world on the subject of aircraft conceptual design. This new edition expands and updates this modern classic including timely topics such as "green aircraft" and electric propulsion, but retains the completeness and readability that have placed it in universities and design offices everywhere. The book covers every topic necessary to the understanding of aircraft design, such as aerodynamics, structures, stability and control, propulsion, etc., with an overview introduction starting from first principles. All are discussed from the point of view of the designer, not the specialist in any given topic area"...